COMPARATIVE ANALYSIS OF TRANSLATION METHODS FOR PUBLICISTIC TEXTS: A SCIENTIFIC EXPLORATION - Munira Isroilovna Absamadova (Web of Journals Publishing, 2023)
This scientific article delves into the intricacies of translating publicistic texts, aiming to provide a comprehensive understanding of the various methods employed in this challenging task. Publicistic texts, characterized by their informative, persuasive, and often emotionally charged nature, pose unique challenges for translators. In this study, we explore and evaluate different translation methods applied to publicistic texts, considering linguistic, cultural, and pragmatic aspects. The article also discusses the impact of technological advancements on the translation process, emphasizing the role of machine translation tools in enhancing efficiency and maintaining fidelity to the original text.
Keywords: Translation methods, linguistic challenges, cultural considerations, machine translation, translation strategies.